HBR's 10 must reads for business students. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"If you read nothing else to stand out in class and prepare for what's next, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the best ones to help you understand the most important ideas in management, feel confident in business school, and thrive in any role you take on. This book will inspire you to: Think more strategically; inspire and execute innovation; develop marketing plans that deliver competitive advantage; perform at your highest personal level; learn with a growth mindset; redefine what career success looks like to you"--
Manage Your Work, Manage Your Life / by Boris Groysberg and Robin Abrahams -- Harnessing the Science of Persuasion / by Robert B. Cialdini -- How to Give a Killer Presentation / by Chris Anderson -- The Science of Strong Business Writing / by Bill Birchard -- How High Achievers Overcome Their Anxiety / by Morra Aarons-Mele -- How to Play to Your Strengths / by Laura Morgan Roberts, Gretchen Spreitzer, Jane E. Dutton, Robert E. Quinn, Emily D. Heaphy, and Brianna Barker -- You're Not Powerless in the Face of Imposter Syndrome / by Keith D. Dorsey -- What Great Managers Do / by Marcus Buckingham -- The Authenticity Paradox / by Herminia Ibarra -- The C-Suite Skills That Matter Most / by Raffaella Sadun, Joseph Fuller, Stephen Hansen, and PJ Neal -- Building an Ethical Career /dr by Maryam Kouchaki and Isaac H. Smith -- From Purpose to Impact / by Nick Craig and Scott A. Snook.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Industrial management; Success in business; Business education; Gestion d'entreprise.; Succès dans les affaires; Enseignement commercial